1979
DOI: 10.1111/j.2044-8295.1979.tb01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotionality in male and female rodents: A reply to Archer

Abstract: Archer (1979) has complained that his criticisms (Archer, 1971, 1973, 1975) of Gray's (1971 a, b) views on emotionality and on sex differences in fearfulness in rodents have not been answered. These criticisms are shown to lack substance and to depend on confused arguments and misleading reviews of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(36 citation statements)
references
References 41 publications
(111 reference statements)
4
32
0
Order By: Relevance
“…In fact, gender differences in emotionality have not been demonstrated in a consistent direction throughout several behavioral models. For example, in the open field males usually show less locomotor activity and higher defecation levels than females [5]. Such results are traditionally interpreted as an indicative that males are more "fearful" or "anxious" than females.…”
Section: Sex Differencesmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, gender differences in emotionality have not been demonstrated in a consistent direction throughout several behavioral models. For example, in the open field males usually show less locomotor activity and higher defecation levels than females [5]. Such results are traditionally interpreted as an indicative that males are more "fearful" or "anxious" than females.…”
Section: Sex Differencesmentioning
confidence: 94%
“…Defecation in the open field was probably one of the first measures of animal emotionality, since this response is closely related with fear and autonomic arousal. Since then, several other animal paradigms of anxiety, mostly with rodents, have been developed (for a review see [3][4][5][6]). These tests consist of exposing an animal to an aversive environment while assessing one or a set of defensive behaviors, according to the innate or learned state characteristics of the threatening situation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the reluctance of rats to explore the open arms of the maze is caused by fear of open spaces, rather than the novelty of the maze or its height (Pellow et al, 1985). The open field test is also a frequently used test of anxiety (Gray, 1979). Both tests have been pharmacologically validated with anxiolytic compounds increasing, and conversely anxiogenic compounds decreasing the percentage of time spent in the open areas (Pellow et al, 1985;Gentsch et al, 1987;Cole et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting behavioral tests for emotionality while separating non-emotional confounding factors, such as motor activity, has been the subject of intense debate 6,7 . As the OFM was originally described, two measures of emotionality can be deduced, locomotor activity and fecal boli deposits or defecation 1 .…”
Section: Introductionmentioning
confidence: 99%